Rare Animal Recognition Applicaton Using Augmented Reality Technology And Marker Based Qr Code - Yulianti, Fintas; Norhikmah, Norhikmah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Indonesia has a rich diversity of animals, but the lack of media to introduce endangered species from various regions such as Java, Sulawesi, Bali, NTT and Kalimantan has led to a lack of awareness of their existence, which has led to the threat of extinction. The purpose of this research is to produce an Android application that utilizes Augmented Reality (AR) technology to introduce endangered species. The MDLC (Multimedia Development Life Cycle) method is used in this analysis, which consists of 6 stages: concept, design, collection of materials, assembly, testing, and finally distribution. The Unity Engine is used as the basis for Android applications. Augmented Reality (AR) is an effective learning tool for early childhood education, especially in the realm of endangered species education. In addition to introducing rare animals, the app will include quizzes as part of the game to increase knowledge about these animals.